Factors Associated with the Pressure Pain Threshold in Healthy Chinese Men. Issue 9 (6th June 2013) - Zhang, Youjie; Zhang, Shijun; Gao, Yong; Tan, Aihua; Yang, Xiaobo; Zhang, Haiying; Wu, Chunlei; Lu, Zheng; Liao, Ming; Xie, Yuangliang; Zhang, Zhifu; Qin, Xue; et al.
Abstract: Objective: The goal of present study was to examine the influence of demographic characteristics, lifestyle, and metabolic factors on pressure‐induced pain threshold. Design and Setting: The study population comprised 2, 517 healthy men at second‐phase recruitment of a population‐based cohort in China. The pressure pain threshold (PPT) at two locations, triceps and inguinal lines, was obtained using a digital pressure algometer. Education and occupation, as well as lifestyle factors, were self‐reported in a face‐to‐face interview. Blood lipid and fasting glucose were measured as a routine healthy check‐up program. Results: A lower PPT was found among men with younger age, higher level of education, and non‐manual occupation. In addition, men with central obesity and moderate leisure time physical exercise were more sensitive to muscle mechanical stimuli. PPT was significantly correlated with high‐density lipoprotein cholesterol (β for triceps = 0.064, and β for inguinal lines = 0.052) in a multivariate linear regression model, after controlling for multiple variables. Elevated PPT was also found among subjects with hyperglycemia (both P for triceps and inguinal lines <0.001) and excess drinking ( P for triceps = 0.005). Conclusions: It is important for physicians and researchers to consider these variables when evaluating pain sensitivity in clinic and in research. The underling mechanisms between these factors and pressure pain perception are worthy of further exploration.